2016
DOI: 10.1021/acs.biochem.6b00890
|View full text |Cite|
|
Sign up to set email alerts
|

Biochemical and Spectroscopic Characterization of the Non-Heme Fe(II)- and 2-Oxoglutarate-Dependent Ethylene-Forming Enzyme from Pseudomonas syringae pv. phaseolicola PK2

Abstract: The ethylene-forming enzyme (EFE) from Pseudomonas syringae pv. phaseolicola PK2 is a member of the mononuclear non-heme Fe(II)- and 2-oxoglutarate (2OG)-dependent oxygenase superfamily. This enzyme is reported to simultaneously catalyze the conversion of 2OG into ethylene plus three CO2 and the Cδ hydroxylation of L-arginine (L-Arg) while oxidatively decarboxylating 2OG to form succinate and carbon dioxide. A new plasmid construct for expression in recombinant Escherichia coli cells allowed for the purificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
79
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(94 citation statements)
references
References 40 publications
7
79
4
Order By: Relevance
“…A recombinant form of the ethylene-forming enzyme from PsEFE was produced in Escherichia coli and purified to near homogeneity. Using NMR and GC/MS-based assays, we found that, as reported (14,21), PsEFE-catalyzed ethylene production is 2OG-dependent, stimulated by the addition of Fe(II) [some Fe(II) likely copurifies with PsEFE], and is increased by the addition of ascorbate or DTT ( Fig. 1 C and D and SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 61%
See 4 more Smart Citations
“…A recombinant form of the ethylene-forming enzyme from PsEFE was produced in Escherichia coli and purified to near homogeneity. Using NMR and GC/MS-based assays, we found that, as reported (14,21), PsEFE-catalyzed ethylene production is 2OG-dependent, stimulated by the addition of Fe(II) [some Fe(II) likely copurifies with PsEFE], and is increased by the addition of ascorbate or DTT ( Fig. 1 C and D and SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 61%
“…2). Formation of the bidentate 2OG intermediate complex I is supported by spectroscopic work (21). Turnover of 2OG to succinate also occurs (Fig.…”
Section: Significancementioning
confidence: 61%
See 3 more Smart Citations